Bilateral agreement for academic years 2012/2016 Lifelong Learning Programme: higher education - Erasmus between Universidade Lusíada de Lisboa and Universidad CEU San Pablo - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the Erasmus programme. - Subject area: Architecture; Business studies; Communication and information sciences; Public relations, publicity, advertising.